Does Risk Based Thinking Matters to Support Business Sustainability A Workshop Provided for Community of Forum Standardisasi Indonesia - Firdaus Basbeth (Journal of Sustainable Community Development (JSCD), 2020)
Risk can appear in any form such as environmental risk, business risk, and health and safety risk. Many companies especially in manufacturing sectors, they are generally familiar with the process of identification, evaluate and control the environmental, health and safety risk predominantly in operational level to keep their process safe for the people and environment. However, when it comes to business risk, the company's understanding, method, and level of implementation should be adjusted to achieve business objectives and fulfill requirements which implied in the new IS 9001:2018 quality standards. Although there are no special requirements for the organization to maintain or retain documented information related to addressing risks and opportunities, organizations can choose to do so and this will be influenced by the size and nature of the organization. Many organizations don’t have a clear understanding of maintaining and managing lists of business risks and opportunities properly. For this reason, equipping oneself with knowledge related to risk-based thinking and risk management is very important. The aim of the workshop is to improve understanding of Risk-Based Thinking in business processes related to their internal and external business context, specifically in risk identification, evaluating the risks that have been identified, managing the risks at every level effectively. The workshop is carried out in third stages: firstly facilitator explains the workshop material, followed by questions and answers, and finally, the workshop participants were involved in a risk identification and risk assessment simulation. The cognitive aspect of the participants was obtained through a pre-test and post-test, showed that understanding of risk-based thinking is increased, as well as the skill to use tools to be used to manage risk.